Quantum dynamics of the H plus ND reaction - Surucu, Seda; Akpinar, Sinan (Elsevier Science Bv, 2012)
Quantum scattering dynamics calculation is used to study initial-state-resolved reaction probabilities, integral cross section, initial state selected reaction rate constants and thermal rate constant for both channels of the reaction ND(a(1)Delta) + H(S-2) -> products on the modified NH2 (A) over tilde (2)A(1) potential energy surface (PES) using centrifugal sudden (CS) approximation. This surface is barrierless and therefore, for depletion channel, probabilities have small centrifugal thresholds and present sharp and large resonances, associated with long-lived collision complexes. Integral cross sections for both reactions depend strongly on initial rotational states. In particular, thermal reaction rate constant for depletion channel is in good agreement with experimental and semiclassical results. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Reaction Probabilities; Wave-Packets; Scattering